2013
DOI: 10.5152/tjbh.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Women about Breast Cancer, Self Breast Examination and Healthy Life Style Behaviours

Abstract: Objective:The present study was conducted to determine the knowledge and attitudes of female students, who have just started to attend university, about breast cancer, self breast examination and healthy life style behaviours. Materials and Methods:This descriptive study consisted of 384 female university students who started to attend Erciyes University in the 2009-2010 academic year. Three hundred and thirty one women were included in the study. Data were collected with an Individual Information Form includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
2
5
0
1
Order By: Relevance
“…These findings are supported by similar studies (13,14). 53.1% of women who participated in our study had knowledge about BSE while 86.4% of women who participated in study conducted by Ozen et al (15) had knowledge about BSE. Forty-four percent of women had CBE at least once throughout their lifetime.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These findings are supported by similar studies (13,14). 53.1% of women who participated in our study had knowledge about BSE while 86.4% of women who participated in study conducted by Ozen et al (15) had knowledge about BSE. Forty-four percent of women had CBE at least once throughout their lifetime.…”
Section: Discussionmentioning
confidence: 61%
“…This condition was associated with the women's level of education. There are significant differences among BSE knowledge, age, education and marital status in many studies (12,15,19,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…35% of the participant students told that they got information on breast cancer before ( Table 2). The rate of those receiving information on breast cancer before was 64.2% in the study by Tahmasebi and Noroozi, 52.4% in study by Segni et al (19) , 50% in the study by Özkahraman et al (20) and 50.2% in the study by Özen et al (21). Therefore, it is very crucial to promote and to enhance awareness level of young women about breast cancer, which has increased in the recent years, to inform women about breast cancer screenings and to help them gain health promoting behaviors (21).…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies revealed that the rates of BSE and mammography are not at the desired level (10)(11)(12)(13)(14)(15)(16)(17). There are numerous factors delaying and obstructing individuals' participation in screenings.…”
Section: Introductionmentioning
confidence: 99%